AB0687 The Frequency of Low Bone Mineral Density in Enteropaty Arthritis. (10th June 2014) - Deliu, C.; Ciurea, P.; Criveanu, C.; Vreju, F.; Ciurea, T.
Abstract : Background: Metabolic bone disease is common in patients with enteropaty arthritis. Objectives: The objective of our study was to determine the frequency of bone loss among patients with enteropathy arthritis and possible contributing risk. Methods: In collaboration with Gastroenterology Clinic all enteropaty arthiritis (Chron's disease and ulcerative colitis) diagnosed from January 2011 to December 2013 were included in the study. Low bone mass, osteopenia, and osteoporosis were defined according to the WHO guidelines. Case notes and bone mass density results were carefully reviewed for demographic and clinical data. Results: Study has included 28 enteropaty arthitis patients; 40% had Crohn's disease and 60% had ulcerative colitis. The average age was 32.4±12.1 years. Using T-scores, the frequency of osteopenia was 49.28%, and the frequency of osteoporosis was 32.48% at both lumbar spine and proximal femur. Only 24.6% of patients exhibited a bone mass density within the normal range. Our results revealed a positive correlation between the Z-score in both the lumbar spine and the proximal femur and body mass index (P=0.039 and P=0.016, respectively). On regression analysis body mass index, age, and calcium supplementation were found to be the most important independent predictors of bone mass density. Conclusions: Body mass index and age were the most important independent predictors of low bone mass density. Patients with enteropaty arthitis are at an increased risk of low bone mass density and the frequency of decreased bone mass density in patients with Crohn's disease and ulcerative colitis were similar. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5366